Age-related trends of inhibitory control in Stroop-like big–small task in 3 to 12-year-old children and young adults - Ikeda, Yoshifumi; Okuzumi, Hideyuki; Kokubun, Mitsuru (Frontiers in Psychology, 2014)
Inhibitory control is the ability to suppress competing, dominant, automatic or prepotent cognitive processing at perceptual, intermediate, and output stages. Inhibitory control is a key cognitive function of typical and atypical child development. This study examined age-related trends of Stroop-like interference in 3–12-year-old children and young adults by administration of a computerized Stroop-like big–small task with reduced working memory demand. This task used a set of pictures displaying a big and small circle in black and included the same condition and the opposite condition. In the same condition, each participant was instructed to say ‘big’ when viewing the big circle and to say ‘small’ when viewing the small circle. In the opposite condition, each participant was instructed to say ‘small’ when viewing the big circle and to say ‘big’ when viewing the small circle. The opposite condition required participants to inhibit the prepotent response of saying the same, a familiar response to a perceptual stimulus. Results of this study showed that Stroop-like interference decreased markedly in children in terms of error rates and correct RT. There was no deterioration of performance occurring between the early trials and the late trials in the sessions of the day–night task. Moreover, pre-test failure rate was relatively low in this study. The Stroop-like big–small task is a useful tool to assess the development of inhibitory control in young children in that the task is easy to understand and has small working memory demand.